Simple hydrothermal synthesis of very-long and thin silver nanowires and their application in high quality transparent electrodes. Issue 29 (5th July 2016) - Bari, Bushra; Lee, Jinhwan; Jang, Taehee; Won, Phillip; Ko, Seung Hwan; Alamgir, Khalid; Arshad, Muhammad; Guo, L. Jay
Abstract : Well dispersed very long and thin silver nanowires are synthesized using glucose as a reducing agent and silver chloride as a silver source. The wire lengths are in the range of 200 to 500 microns with an average diameter of 45–65 nm. Abstract : Solution-processed silver nanowire (AgNW) random mesh is a strong contender to commercial indium tin oxide (ITO); however, its performance is limited due to large contact resistance between nanowires and post-processing treatments. As an alternative, long nanowires can decrease the number of contact points and contact resistance. Here, a simple modified hydrothermal method for the synthesis of very-long silver nanowires (AgNWs) and their use in a high quality transparent conducting electrode without post-processing has been developed. Well dispersed very-long and thin silver nanowires are synthesized by using glucose as a reducing agent and silver chloride as a silver source. The lengths of the wires are in the range of 200 to 500 μm with an average diameter of 45–65 nm. To the best of our knowledge, this is the first report on long nanowires having a thin diameter with greater than 200 microns length. As compared to other transparent conductors and nanowire networks, this AgNW network shows a higher percolative figure of merit (FoM, Π ) with low haze. A flexible touch screen using the AgNW network is also demonstrated which has shown good performance even on a bendable surface.